DAMPAK PEDAGANG KECIL TERHADAP ADANYA RITEL DESA SRUMBUNG KECAMATAN SRUMBUNG KABUPATEN MAGELANG JAWA TENGAH - Suparna Suparna (Cakrawala - Jurnal Humaniora, 2020)
With the presence of large-scale retail traders in Srumbung Village, the community, especially small traders in Srumbung Village, did not rule out new problems in the village, competition with small traders will certainly occur due to friction arising from the emergence of many new traders, besides competing to make their merchandise sellable, the problem is that the income level will definitely be greatly reduced. The method that the writer uses in this study uses a descriptive qualitative method by interpreting relying, using the formulation of the problem of how the impact of small traders with the presence of large-scale retailers of merchants in Srumbung Village, Srumbung District, Magelang Regency, Central Java. On this occasion the authors convey the results of the discussion in accordance with the title already stated above, that the impact of small traders with the presence of retail retailers on a large scale, is very unsettling for small traders who are in Srumbung Village, both at the level of captivity every day and bring about changes in the culture of the community , from traditional culture to modern culture with an instant lifestyle.